The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.chemmater.8b01624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catalyst Phase on the Hydrogen Evolution Reaction of Water Splitting: Preparation of Phase-Pure Films of FeP, Fe2P, and Fe3P and Their Relative Catalytic Activities

Abstract: The comparative catalytic activities of iron phosphides, Fe x P (x = 1-3), have been established with phase-pure material grown by Chemical Vapor Deposition (CVD) from single-source organometallic precursors. This is the first report of the preparation of phase-pure thin films of FeP and Fe 2 P and their identity was established with scanning-electron microscopy, X-ray photoelectron spectroscopy, and powder X-ray diffraction. All materials were deposited on fluorine-doped tin oxide (FTO) for evaluation of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 62 publications
1
67
0
Order By: Relevance
“…Meanwhile, the computational simulation of HER process revealed that hydrogen tends to be stable at the bridging sites of Mo instead of P sites, thus engendering an ideal hydrogen adsorption Gibbs‐free energy on Mo 3 P (110) surface (Figure i). Besides, Schipper et al also observed a similar phenomenon in various stoichiometric ratios Fe‐based phosphides thin films . In their work, the HER activities followed the trend Fe 3 P>Fe 2 P>FeP because metal‐rich phosphides (Fe 3 P and Fe 2 P) surface had higher hydrogen coverages under thermoneutral hydrogen absorption conditions.…”
Section: Modulated Strategies For Tmps In Electrocatalytic Her Oer mentioning
confidence: 60%
“…Meanwhile, the computational simulation of HER process revealed that hydrogen tends to be stable at the bridging sites of Mo instead of P sites, thus engendering an ideal hydrogen adsorption Gibbs‐free energy on Mo 3 P (110) surface (Figure i). Besides, Schipper et al also observed a similar phenomenon in various stoichiometric ratios Fe‐based phosphides thin films . In their work, the HER activities followed the trend Fe 3 P>Fe 2 P>FeP because metal‐rich phosphides (Fe 3 P and Fe 2 P) surface had higher hydrogen coverages under thermoneutral hydrogen absorption conditions.…”
Section: Modulated Strategies For Tmps In Electrocatalytic Her Oer mentioning
confidence: 60%
“…The peak at 707.2 eV is assigned to FeP specie, which is in agreement with the XRD pattern (Fe 2 P). Another peak at 715.7 eV is FeO specie due to the surface oxidation upon the exposure to air . Figure e (P 2p) shows three peaks at 127.9, 129.8, and 134.8 eV which are indexed to FeP (2p 3/2 ), FeP (2p 1/2 ), and FePO species, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…The same motivation led Schipper and coworkers to grow FeP, Fe 2 P, and Fe 3 P thin films recently. 104 The films were grown by metal-organic chemical vapor deposition using single-source molecular precursors (Fe(CO) 4 PH 3 ) on fluorine-doped tin oxide to evaluate the system performance in hydrogen evolution. Both the experimental and the density functional theory calculations results show a higher hydrogen coverage for Fe-rich nanoparticles in comparison with P-rich.…”
Section: F Fe 2 P Familymentioning
confidence: 99%